CH2OO Criegee intermediate UV absorption cross-sections and kinetics of CH2OO + CH2OO and CH2OO + I as a function of pressure. Issue 17 (21st April 2020) - Mir, Zara S.; Lewis, Thomas R.; Onel, Lavinia; Blitz, Mark A.; Seakins, Paul W.; Stone, Daniel
Abstract : The UV absorption cross-sections of the Criegee intermediate CH2 OO, and kinetics of the CH2 OO self-reaction and the reaction of CH2 OO with I are reported as a function of pressure at 298 K. Abstract : The UV absorption cross-sections of the Criegee intermediate CH2 OO, and kinetics of the CH2 OO self-reaction and the reaction of CH2 OO with I are reported as a function of pressure at 298 K. Measurements were made using pulsed laser flash photolysis of CH2 I2 /O2 /N2 gas mixtures coupled with time-resolved broadband UV absorption spectroscopy at pressures between 6 and 300 Torr. Results give a peak absorption cross-section of (1.37 ± 0.29) × 10 −17 cm 2 at ∼340 nm and a rate coefficient for the CH2 OO self-reaction of (8.0 ± 1.1) × 10 −11 cm 3 s −1, with no significant pressure dependence of the absorption cross-sections or the self-reaction kinetics over the range investigated. The rate coefficient for the reaction between CH2 OO and I demonstrates pressure dependence over the range investigated, with a Lindemann fit giving k 0 = (4.4 ± 1.0) × 10 −29 cm 6 s −1 and k ∞ = (6.7 ± 0.6) × 10 −11 cm 3 s −1 . The origins of IO in the system have been investigated, the implications of which are discussed.